Moon hunt - Gear, W. Michael; Gear, Kathleen O'Neal (Gear, W. Michael. Morning star., 2017)
What happens when your god goes missing? The lord god of Cahokia has been spirited away to the Underworld and the empire teeters on the brink of disaster as clans fight for control. Night Shadow Star, the god<U+2019>s human sister, and Fire Cat, her warrior bodyguard, are the only two people who can bring him back. They descend into the Sacred Cave where monsters dwell, willing to sacrifice themselves to save their kingdom. What they find makes them question if that sacrifice is worth it.